An optical image stabilisation using a droplet manipulation on a liquid crystal and polymer composite film. Issue 13 (7th December 2016) - Wang, Yu-Jen; Tsou, Yu-Shih; Chen, Ming-Syuan; Lin, Yi-Hsin
ABSTRACT: We demonstrate an image system with an optical image stabilisation using a droplet manipulation on a liquid crystal (LC) and polymer composite film (LCPCF) to reduce motion blur while preserve image quality. Such an image system adopts a liquid lens on an LCPCF and the mechanism is on a basis of droplet movement on LCPCF whose position changes because electrically tunable orientations of LC molecules on the surface of LCPCF. The change of position of the liquid lens compensates the deviation of light as the image system is under a handshake vibration. As a result, the image system under handshake vibrations could keep a clear image. The operating principles are introduced, and the experiments are performed and discussed. The concept in this paper can also be extended to design other optical components for modulating direction of light. GRAPHICAL ABSTRACT: